TEACHING AND LEARNING PROCESS OF SPEAKING - Susanty, Henny; Ritonga, Dewi; Tursina, Puan (Getsempena English Education Journal, 2017)
This study was investigated the process of language teaching and learning of speakingÂ  in terms ofÂ  teaching materials, teaching methods and learning assessments to the studentsâ at MTsN Blangpidie in the Academic years of Â 2016/2017. This studyÂ  was a descriptiveÂ  research. Two English teachers who taught at MTsN Blangpidie were participated in this study. An Interview was used to collect the data. The data were recorded, transcribed and coded based on the the problems. The finding of the study showedÂ  that the teachers at MTsN Blangpidie ofÂ  South West Aceh used various teaching materials, teaching strategies and also learning assessments.Â Keywords: Speaking, Teaching Materials, Teaching Methods and Learning Assessments